Molecular Mechanisms in the Carcinogenesis of Oral Squamous Cell Carcinoma: A Literature Review - Laertty Garcia de Sousa Cabral; Isabela Mancini Martins; Ellen Paim de Abreu Paulo; Karina Torres Pomini; Jean-Luc Poyet; Durvanei Augusto Maria (Biomolecules)
The tumor microenvironment (TME) plays a crucial role in the development, progression, and metastasis of oral squamous cell carcinoma (OSCC). The TME comprises various cellular and acellular components, including immune cells, stromal cells, cytokines, extracellular matrix, and the oral microbiome, all of which dynamically interact with tumor cells to influence their behavior. Immunosuppression is a key feature of the OSCC TME, with regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), and tumor-associated macrophages (TAMs) contributing to an environment that allows tumor cells to evade immune surveillance and supports angiogenesis. The oral microbiome also plays a pivotal role in OSCC pathogenesis, as dysbiosis, or imbalances in the microbiota, can lead to chronic inflammation, which promotes carcinogenesis through the production of pro-inflammatory cytokines and reactive oxygen species (ROS). Pathogens like Porphyromonas gingivalis and Fusobacterium nucleatum have, hence, been implicated in OSCC-driven tumor progression, as they induce inflammation, activate oncogenic pathways, and modulate immune responses. In this review, we discuss how the interplay between immunosuppression and microbiome-driven inflammation creates a tumor-promoting environment in OSCC, leading to treatment resistance and poor patient outcomes, and explore the potential therapeutic implication of a better understanding of OSCC etiology and molecular changes.